(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The main purpose of the research is to identify the degree to which the high containment practices contribute to organizational health. The two years are the main driver of all the successes of contemporary organizations. Therefore, it is necessary to contain this important resource. Regulatory health is one of the indicators of success in its ability to invest its resource in the best possible way. And adapt to the changes that occur in the variables of the environment, so the importance of research in trying to provide a range of solutions to the problems facing the Organization in this area. The research problem also indicated a clear lack of importance in the use of these practices in strengthening the organizational health of the organization. The researcher adopted the analytical descriptive method in the applied side of the research. The questionnaire was adopted as a main tool for collecting research data, which was prepared based on the ideas of a number of previous measurements. The sample was distributed to 132 employees of the General Company for Iraqi Vegetable Oils (SPSS) and (EXCEL) in the introduction and analysis of research data, has resulted in the statistical tools used in the analysis of a set of results confirmed the existence of correlation relationship and significant impact among the variables investigated on the basis of which were accepted the main hypotheses and sub - The researcher concluded that the organization in question is taking a clear interest in how to benefit from the high containment practices in strengthening its organizational health, and therefore recommended that the experiences of the developed countries in the field should be examined and try to employ the results of their experiences in the organization in question.